2019
DOI: 10.1007/s11240-019-01613-7
|View full text |Cite
|
Sign up to set email alerts
|

mRNA transcription profile of potato (Solanum tuberosum L.) in response to explant cutting

Abstract: The explant is an important parameter in plant tissue culture. Most plant tissue culture studies in the literature have focused almost exclusively on the use of explants as a tool for organogenesis or (micro)propagation, and there is limited information that documents the changes that occur in explants in response to cutting during explant preparation just prior to or during culture. To better understand the molecular changes occurring during the wounding process that accompanies the preparation of an explant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The application of the same analyses to other plant systems would allow for an understanding if these patterns exist in other plant species. A recent study (Teixeira da Silva et al 2019) that essentially employed identical methodology as was used in this study, found that, as in this study, several stress-related DEGs were both up- and down-regulated in cut potato explants relative to intact 4 w plantlets.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The application of the same analyses to other plant systems would allow for an understanding if these patterns exist in other plant species. A recent study (Teixeira da Silva et al 2019) that essentially employed identical methodology as was used in this study, found that, as in this study, several stress-related DEGs were both up- and down-regulated in cut potato explants relative to intact 4 w plantlets.…”
Section: Discussionsupporting
confidence: 64%
“…The entire methodology (between “Total RNA isolation and removal of rRNA” and “Protein analysis by two-dimensional (2-D) gel electrophoresis”), save for minor differences, has been reported verbatim in a paper that recently examined the effect of cutting on explant transcriptomic profile (Teixeira da Silva et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Using the methodology reported earlier Teixeira da Silva et al 2019), total protein was extracted from the five samples (0 h, 24 h, 48 h, 1 week, 4 weeks) in three biological replicates from each sample and analyzed using the Agilent Protein 230 Kit (Agilent, Santa Clara, CA, USA) on an Agilent Bioanalyzer 2100 (Agilent) both under reducing (dithiothreitol) and nonreducing (distilled water) conditions.…”
Section: Protein Analysis By Two-dimensional (2-d) Gel Electrophoresismentioning
confidence: 99%
“…5A, B). Actin has been routinely used by many research groups as a reference gene in gene expression studies [40,41,[105][106][107][108][109][110][111][112][113]. Our results raised questions on the validity of conclusions of earlier reports where actin was used as a reference gene in analysis involving grapevine and viral infections.…”
Section: Novel Reference Genes Outperformed Traditional Reference Genes In Transcripts Quantificationmentioning
confidence: 66%